Model Determinan Kebijakan Hutang dan Nilai Perusahaan (Studi Pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia) - Sri Puji Lestari; Dahrani Dahrani; Nadia Ika Purnama; Jufrizen Jufrizen (Maneggio: Jurnal Ilmiah Magister Manajemen, 2021)
This study aims to determine the determinants of debt policy and firm value (Study on Pharmaceutical Companies Listed on the Indonesia Stock Exchange). The research approach uses an associative approach. This research was conducted on the Indonesia Stock Exchange (IDX), especially pharmaceutical sector companies on the Indonesia Stock Exchange (IDX) in 2015-2019. The population used in this study is the pharmaceutical sector companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019, amounting to 10 companies. The sample of this study were 8 pharmaceutical companies listed on the Indonesia Stock Exchange (IDX). The collection technique uses documentation techniques. Data analysis using Path Analysis or Path Analysis. institutional ownership has a negative and insignificant effect on firm value, firm size has a positive and insignificant effect on firm value. institutional ownership has a negative and insignificant effect on debt policy, firm size has a positive and significant effect on debt policy, debt policy has a negative and insignificant effect on firm value, institutional ownership on firm value through debt policy has no significant effect and firm size on firm value through debt policy has no significant effect.